Cultural heritage related to the Mongols of the Ilkhanate in Erzurum - Tsogbadrakh , Ulaanaa; Mijiddorj , Enkhbaatar (Mongolian Journal of Arts and Culture, 2025)
The city of Erzurum in Türkiye is home to two architectural masterpieces that are considered invaluable cultural and historical heritage and ancient works of art: Hasan Castle and Çobandede Bridge. Located on the eastern edge of Anatolia and on the historical Silk Road, Erzurum is one of Türkiye’s current border cities and has long been considered a region of significant geopolitical importance. At the heart of this city are two important architectural landmarks: the Twin Minaret Madrasa (Hatuniye Madrasa, 1285-1290) and the Yakutiye Madrasa (1310-1311). Scholars have noted that these structures have transformed Erzurum into a city famous for its history and architecture. In addition, landmarks such as Hasan Castle and Çobandede Bridge, dating back to the Ilkhanate period, serve as evidence of the historical heritage left in this city by the Mongols. Эрзурум хот дахь Ил хаант улсын соёлын дурсгал Хураангуй: Бүгд Найрамдах Турк Улсын Эрзурум хотын түүхийн үнэт дурсгал, соёлын биет өв, эртний урлагийн бүтээлд тооцогдож буй хоёр уран барилга, Хасан цайз Чобандеде гүүрийн тухай авч үзсэн болно. Турк улсын хилийн хотуудын нэг Эрзурум нь торгоны замын чухал бүс болж, Анатолийн зүүн хязгаарт оршиж эртнээс өнөөг хүртэл геополитикийн хувьд ч өндөр ач холбогдолтой хот байсаар иржээ. Хотын төвд Хос баганат сүм/Хатуниеэ медресе (1285-1290), Якутиеэ медресе (1310-1311) хэмээн нэрлэгдэх хоёр уран барилга байх нь Ил хаант улсын монголчуудын бүтээн байгуулалтын жишээ бөгөөд судлаачид Эрзурумыг хот болгон хувиргасан уран барилга, түүхийн дурсгал гэж тэмдэглэжээ. Мөн Хасан цайз Чобандеде гүүр зэрэг Ил хаант улсын үед хамаарах буюу Монголчуудын үлдээсэн дурсгалууд энэ хотод бий юм. Түлхүүр үгс: Эрзурум, Хос баганат сүм, Якутиеэ медресе, Ил хаант улс, Ил хан